Novel hybrid coupling of ecohydrology and socioeconomy at river basin scale: A watershed system model for the Heihe River basin. (July 2021) - Li, Xin; Zhang, Ling; Zheng, Yi; Yang, Dawen; Wu, Feng; Tian, Yong; Han, Feng; Gao, Bing; Li, Hongyi; Zhang, Yanlin; Ge, Yingchun; Cheng, Guodong; et al.
Abstract: Watershed system models are important tools for understanding complex watershed systems and integrated river basin management. However, there are very few models that can represent the coevolution of water, ecology and socioeconomic system at the river basin scale. In this study, a watershed system model was developed using the case of the Heihe River basin (HRB), a typical endorheic river basin in Northwest China. The model is mainly composed of an integrated ecohydrological model, a socioeconomic model, and two interface models. It has been embedded into a decision support system using the surrogate modeling technique. The watershed system model proved to be reliable in simulating multiple eco-hydrological processes, and showed good abilities in exploring the trajectories and interactions of water, ecology and socioeconomy. This study advances our understanding of the water-land-air-plant-human nexus at the watershed scale, and has great implications for sustainable developments in endorheic river basins. Highlights: A watershed system model was developed by coupling ecohydrological and socioeconomic systems. Trajectories and interactions of water, ecology and socioeconomy were simulated at river basin scale. Critical water resource management issues were investigated using the watershed system model. A decision support system was built based on the watershed system model using surrogate modeling.